The peculiarities of thiol-disulfide metabolism in patients with diabetes mellitus and pulmonary tuberculosis - L.D. Todoriko; E.V. Lesnic; I.O. Semianiv; V.I. Pankiv; O.S. Shevchenko; T.I. Domanchuk (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Background. Glutathione (L-gamma-glutamyl-L-cysteinyl-glycine, GSH) and the enzymes of the glutathione cycle play an important role in the immune response against Mycobacterium tuberculosis infection. The purpose of the study was to assess the main peculiarities and differences of the thiol-disulfide metabolism in patients with drug-susceptible and multidrug-resistant tuberculosis (MDR-TB) developed on the background of diabetes mellitus (DM). Materials and methods. A prospective case-control study was conducted between 2018 and 2022 and included 173 TB patients divided into 3 groups: 1st study group (N = 54) — new cases of drug-susceptible tuberculosis and DM; 2nd study group (N = 56) — new cases of MDR-TB and DM; 3rd study group (N = 63) — non-diabetic patients with progressive TB. These groups were compared with a control group of 36 healthy people. The investigations were conducted according to the national protocol and biochemical assessment standards. Results. In diabetic TB patients, the antioxidant status was enhanced according to the biomarkers, such as total GSH, free –SH groups, total –SH groups, GST, SOD, CAT, GPO, and GR, compared to non-diabetic TB patients. This suggested the existence of an imbalance between oxidants and antioxidants in favor of oxidants. No statistical difference was revealed when comparing the GSH system biomarkers in patients with drug-resistant and susceptible TB. Conclusions. The antioxidant defense was more depleted in diabetic patients, with a greater decrease in MDR-TB group. In non-diabetic TB patients, the total and reduced GSH did not differ compared to healthy individuals, while free –SH groups, total –SH groups, GST, SOD, CAT, GPO, and GR were lower. Even the GSH metabolism biomarkers were lower in the group of patients with drug-resistant TB; the statistical difference was not achieved.